Evaluation of the hygienic sanitary conditions in the elaboration of artisanal alcohol in Manabi - Nevárez-Loor, Gissela (2021)
The production of sugar cane liquor is an activity developed since ancient times in the province of Manabi, practiced through family generations as primary economic income source. This research had as an objective to assess the sanitary hygienic conditions in the production of artisan sugar cane liquor in the province of Manabí. To data collection 40 samples from sugar cane producers were gathered. An initial assessment of sanitary conditions of producing facilities were accomplished. An evaluation tool based on the requirements of the Ecuadorian National Sanitary Authority (ARCSA) for foods and drugs was developed, according to ARCSA-DE-067-2015-GGG rule, which considers issues related with facilities and equipment, personnel hyginie and production operations. According to the variance analysis there are significative differences, so samples do not comply with the requirements established by the national sanitary authority, which derives in a lack of safety in the final product, being this a risk to health for sugar cane liquor consumers.